Pregnancy-Related Information Need and Information-Seeking Pattern Among Pregnant Women Attending Antenatal Clinic at Ikorodu General Hospital, Lagos State, Nigeria - Foluso, Ojewole,; O., Oludipe, Yemisi (European Scientific Journal, ESJ, 2017)
Background: Pregnant women attending antenatal care have a need for quality pregnancy-related information. Purpose: To describe the pregnancy-related information seeking patterns among pregnant women attending antenatal clinic in Ikorodu. Methods and Design: The study was carried out using a descriptive correlational design. A purposive sample of 228pregnant women were recruited from an antenatal clinic in Lagos State to complete pregnancy-related information seeking pattern questionnaire (PRISPQ).” Descriptive analysis and inferential statistics (logic regression) was used to analyse the information generated. Result: Over 50% respondents are in third trimester, age range 26-35years. Majority of the pregnant women in the study area had moderate level of pregnancy information needs (58.3%, mean = 28.007) and information-seeking (52.2%, mean = 26.119). Long wait to see the healthcare personnel (64.5%) and having knowledge of pregnancy (60.5%) are perceived barriers to seeking pregnancy-related information. The most potent predictor of information seeking pattern among the predictor variables of the study is religion (β = .372; t = 8.419; p < .05), followed by age (β= .300; t = 6.335; p <.05), and lastly by marital status (β= .261; t = 4.456; p <.05). Conclusion: Pregnancy outcomes could be improved if pregnant women are provided with pregnancy-related information necessary to empower them to overcome pregnancy challenges. Thus, nurses and midwives should offer quality information that could assist the pregnant women to make rightful healthcare decision during antenatal.